İBN METTEVYH ve et-TEZKİRE fi AHKAMİ’L-CEVÂHİR VE’L-A’RÂZ ADLI ESERİ ÜZERİNE - Cemalettin Erdemci (İslami İlimler Dergisi)
Ibn Metteveyh who is one of the students of Kâdî Abdülcebbâr is one of the important representative of Basra school of Mutezile. Ibn Metteveyh has written many articles in the field of Islamic theology. Some of these articles have been published and some of them has not been published as yet. However, Ibn Metteveyh is not adequately recognized in Turkey. In this study, we tried to discuss Ibn Mettevey and his theological opinions based on his book entitled “et-tezkire fi ahkâmiil-cevâhir ve’l-a’râz”.